TECHNOLOGY METHODS OF PURIFICATION OF ARTESIAN WATERS ULTRAFILTRATION AND REVERSE OSMOSIS - Mavlanova , Yulduz; Sabirova, Dildora; Djamankulov, Shodiyor (Innovative Development in Educational Activities, 2023)
Reverse osmotic water purification and ultrafiltration are methods of removing foreign impurities, heavy metal salts and organic inclusions from the liquid. The technology is based on the process of membrane separation by means of a semi–permeable membrane through which water passes under high pressure. Ultrafiltration, osmosis – methods of purification of artesian waters and waters from surface sources, which are based on the passage of liquid through a semi-permeable membrane under pressure.